Dynamic Model of Firm Value: Evidence from Indonesian Manufacturing Companies - Kemas Muhammad Husni Thamrin; Syamsurijal Syamsurijal; Sulastri Sulastri; Isnurhadi Isnurhadi (Faculty of Economics, Universitas Sriwijaya, 2018)
This study aims to determine the factors that affect to firm value. The data used in this study is secondary data obtained from the Indonesia Stock Exchange which includes financial statements. This research sample uses 45 manufacturing companies, the period 2012-2016. The analysis used is a quantitative approach with panel data regression model, with estimation of fixed effect model. The findings of this study indicate that simultaneously the value of firms is influenced by investment decisions, financial decisions, and financial performance. While partially, financing decision has dominant influence from other variables, namely investment decision dan corporate performance. The conclusions of this study indicate that investment decisions and firm performance have a positive relationship to firm value, while financing decisions have a negative effect on firm value. In addition, the lag of firm value shows the long-term impact on the firm's value model.